Experimental circular phased array for generating OAM radio beams. Issue 20 (1st September 2014) - Bai, Q.; Tennant, A.; Allen, B.
Abstract : A circular phased array antenna that can generate orbital angular momentum (OAM) radio beams in the 10 GHz band is described. The antenna consists of eight inset‐fed patch elements and a microstrip corporate feeding network. A full‐wave electromagnetic simulator is used to aid the antenna design and theoretical simulations are confirmed by measurements.